Ai based management information system to develop superior human resources in the society 5.0 - Fidela Berliani Prasaja Putri; Nang Among Budiadi; Waluyo Budi Atmoko (Institute of Accounting Research and Novation (IARN), 2026)
The rapid advancement of digital technology in the era of Society 5.0 has encouraged organizations to transform their human resource management practices through the integration of Artificial Intelligence (AI) into Management Information Systems (MIS). This study examines the influence of AI-based Management Information Systems on the development of high-quality human resources, with AI utilization positioned as a mediating variable. A quantitative explanatory approach was employed, using a survey method involving employees and human resource practitioners in organizations that have implemented AI-supported systems. Data were collected through a structured questionnaire measured on a five-point Likert scale to analyze the relationships among the proposed variables. The findings indicate that AI-based Management Information Systems have a positive and significant effect on the development of competitive and adaptive human resources. Furthermore, the effective utilization of AI strengthens the relationship between talent management practices—such as recruitment, training and development, performance management, and employee engagement—and improvements in employee competence, creativity, adaptability, and organizational commitment. These results highlight the strategic importance of integrating AI into human resource systems to enhance organizational competitiveness and sustainability in the Society 5.0 era. This study contributes to the development of a technology-driven human resource management framework relevant to the Indonesian organizational context.).